INSTRUMENTOS MUSICALES PRECOLOMBINOS: LA “ANTARA” O LA FLAUTA DE PAN ANDINA EN EL FORMATIVO FINAL (300 A.C.) E INTERMEDIO TEMPRANO (100.C.) - Sánchez Huaringa, Carlos D. (2017)
Music in pre-Hispanic Peru, from the period of regional growth or also called the Early Intermediate is represented mainly by the Mochica and Nazca societies and also means the maximum development of the musical instruments based on the most symbolic aerophones of the Andean world: the flutes of Bread (antaras) and “quenas”. Thus, the Mochicas would have known (invented?) The complementary dual Pan flute and the Nazca society, the “antaras” in play separated by halves (octave distance) in addition to an unequaled technique in ceramics for the elaboration of these instruments.